VERBA VOLANT, SCRIPTA MANENT: JACQUES'AS DERRIDA IR TIPOGRAFINĖ SEKULIARIZACIJA. - VIDAUSKYTĖ, LINA (Logos: A Journal, of Religion, Philosophy Comparative Cultural Studies & Art (08687692), 2015)
The article deals with jacques derrida's relationship with religion and faith through the perspective of orality, literacy and printing technology. deconstruction is applicable only for the printed word, so all derrida's thought depends on printing technology. According to psychosexual stages of development (oral, anal, phallic) which were described by Sigmund Freud, a parallel can be seen with three-communication technology - oral word, writing, and the printing press. the printed word always commands and controls, in contrast with the oral word. For a long time Learned Latin was such paradigm of control in Western Europe. One might say that Learned Latin as the language of the Father is the crucial factor of control. this paradigm of control is the framework of derrida's thought and a part of his deconstruction method. derrida discovered the philosophical potentialities of cinema at the end of his life. Ghosts appearing in the cinema (which according to Sigmund Freud is nothing else but the parents), and allowed derrida to understand his own philosophical position. In addition, the ghost, i.e. voice, can be interpreted as the return of orality. Secondary orality is the sign of contemporary audiovisual technologies. long live ghosts as derrida's “motto" expresses not only his own reconciliation with the phantasm but at the same time refers to a certain moment of secularity. under the presure of writing, religion was gradually transformed and the printing technology eventually led to the secularization.